Pressupostos de incidência do imposto de importação no direito brasileiro - Sehn, Solon (2015)
After a literature review and a critical analysis of existing theories, the thesis presents a new theory concerning the imposition of the tax on import under the Brazilian law. The study, based on a hypothetic-deductive method, concluded that the tax rule has as material criterion the behavior of import (verb) goods (complement), or the act of introducing goods into the national territory with the intention of incorporated into them. The space criterion is the Customs territory. The time criterion is the moment when a person did or should have done the registration of customs declaration. The creditor (active subject) is the Federal Union, while the debtor (passive subject) is the importer. The customs duties shall be calculated on an ad valorem basis consistent with the methods of valuation established by the GATT Valuation Code. The rate of duty, on the other hand, vary according the origen and the nomenclature under which particular goods should be classified